Sub-ungual Glomus Tumor: Study of 20 Cases - Uddin, Md Maiyeen; Biswas, Swapan Kumar; Rahman, Md Habibur; Karmakar, Narayan Chandra; Rahman, Md Masudur; Alam, Syed Asif Ul; Mondal, Anadi Ranjan (Faridpur Medical College Journal, 2017)
Glomus tumors are benign hamartoma of glomus body. It accounts 1-5% of all soft tissue tumors of hand. They can cause recurrent episodes of intense lancinating pain and disability. Patients often undergo undiagnosed or misdiagnosed for many years because the tumors are small. Twenty patients were operated during the period of 2010 to 2015. Most of the cases were selected on the basis of clinical diagnosis. The help of magnetic resonance imaging was taken in suspicious cases. The only treatment of glomus tumor is total surgical excision. In this study surgical excision were performed by direct trans-ungual approach. All patients showed dramatic relief of pain after surgical excision. Early diagnosis and surgical excision decreases patient's sufferings from severe pain and disability. Eagerness in early diagnosis and surgical excision can reduce long period of sufferings. Faridpur Med. Coll. J. Jul 2017;12(2): 64-67